ALL FALLING FAITHS;REFLECTIONS ON THE PROMISE AND FAILURE OF THE 1960S - J. HARVIE WILKINSON III
In this warm and intimate memoir Judge Wilkinson delivers a chilling message. The 1960s inflicted enormous damage on our country; even at this very hour we see the decade's imprint in so much of what we say and do. The chapters reveal the harm done to the true meaning of education, to our capacity for lasting personal commitments, to our respect for the rule of law, to our sense of rootedness and home, to our desire for service, to our capacity for national unity, and to our need for the sustenance of faith. Judge Wilkinson seeks not to lecture but to share, in the most personal sense, what life was like in the 1960s and to describe the influence of those frighteningly eventful years upon the present day. Judge Wilkinson acknowledges the good things accomplished by the Sixties and nourishes the belief that from that decade we can learn ways to build a better future. But he asks his own generation to recognize its youthful mistakes and pleads with future generations not to repeat them. The author's voice is one of love and hope for America. Our national prospects depend on facing honestly the full magnitude of all we lost during one momentous decade and of all we must now recover.